Implementation of Maqashid Syariah Principles in Islamic Microfinance Practices in Indonesia - Muhtadi, Muhamad Ammar; Author, Muhammad Nailul (Westscience Press, 2025)
This study examines the implementation of Maqashid Syariah principles in Islamic microfinance practices in Indonesia. Using a quantitative approach, data were collected from 64 respondents through a structured questionnaire measured on a 5-point Likert scale. The data were analyzed using SPSS version 25, applying descriptive statistics, validity and reliability tests, correlation, and regression analysis. The findings indicate that Islamic microfinance institutions (IMFIs) in Indonesia generally demonstrate a high level of alignment with Maqashid Syariah principles, particularly in the preservation of wealth (mal) and life (nafs). Regression analysis revealed that these two dimensions are the most influential in shaping microfinance practices, while intellect (‘aql) was found to be relatively less emphasized. The results highlight that IMFIs not only provide Sharia-compliant financial services but also contribute significantly to social welfare, poverty alleviation, and ethical financial inclusion. However, the study suggests that greater efforts are needed to strengthen educational and literacy initiatives to enhance clients’ long-term empowerment. Overall, the findings reinforce the role of IMFIs as vital institutions that integrate economic, social, and spiritual objectives in line with the vision of Islamic economics.